The Effect of Institutional Ownership, Managerial Ownership, Audit Committee, Audit Quality, and Audit Tenure on Financial Statement Integrity - Kurniawati, Fitri; Trisnawati, Rina; Fatchan, Fuad Hudya (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to examine the effect of institutional ownership, managerial ownership, audit committee, audit quality, and audit tenure on the integrity of financial statements. This type of research is quantitative research. The population in this study were manufacturing companies in the consumer goods sector listed on the IDX for the period 2019- 2022. The sampling technique used in this study was purposive sampling and the final result of the data sample was 38 data with a research period of 4 years, so that the sample used was 138 data. Data analysis methods using SPSS by testing multiple linear regression analysis methods. The test results and analysis of research data obtained the conclusion that the audit quality variable has a significant positive effect on the integrity of financial statements variable. While the variables of institutional ownership, managerial ownership, audit committee and audit tenuree have no significant effect on the integrity variable of financial statements.